Using G-Theory to Enhance Evidence of Reliability and Validity for Common Uses of the Paulhus Deception Scales. (January 2018) - Vispoel, Walter P.; Morris, Carrie A.; Kilinc, Murat
We applied a new approach to Generalizability theory (G-theory) involving parallel splits and repeated measures to evaluate common uses of the Paulhus Deception Scales based on polytomous and four types of dichotomous scoring. G-theory indices of reliability and validity accounting for specific-factor, transient, and random-response measurement error supported use of polytomous over dichotomous scores as contamination checks; as control, explanatory, and outcome variables; as aspects of construct validation; and as indexes of environmental effects on socially desirable responding. Polytomous scoring also provided results for flagging faking as dependable as those when using dichotomous scoring methods. These findings argue strongly against the nearly exclusive use of dichotomous scoring for the Paulhus Deception Scales in practice and underscore the value of G-theory in demonstrating this. We provide guidelines for applying our G-theory techniques to other objectively scored clinical assessments, for using G-theory to estimate how changes to a measure might improve reliability, and for obtaining software to conduct G-theory analyses free of charge.